Chemical communication in wild Norway rats: (Rattus norvegicus Berkenhout) - Landete-Castillejos, Tomás (1997)
This study examined the urine and faecal scent marking behaviour and investigatory responses of wild Norway rats (Rattus norvegicus Berkenhout) kept in large, semi-natural enclosures to assess the role these scents play in their communication system.